How to build your team for innovation? A cross‐level mediation model of team personality, team climate for innovation, creativity, and job crafting - Xu, Xiaohong; Jiang, Lixin; Wang, Hai‐Jiang (Journal of occupational and organizational psychology, 2019)
Although multiple theories propose that team proactive personality shapes team climate for innovation, this theoretical proposition is yet to be tested by empirical studies. Drawing upon multiple theories (e.g., sense‐making theory and theories regarding social norms), we hypothesized a cross‐level mediation model of the effects of different operationalizations of team proactive personality on team climate for innovation, as well as individual creative performance and job crafting. We tested our hypothesized model using a 2‐wave longitudinal design collecting data from a sample of 187 employees and their supervisors nested within 38 teams from an Information Technology company. The results of multilevel mediation path analysis indicated that team proactive personality (i.e., mean, minimum, and maximum) was significantly and positively related to team climate for innovation. Further, team proactive personality at Time 1 exerted a cross‐level influence on individual creative performance (rated by supervisors) and job crafting at Time 2, through team climate for innovation. Finally, different operationalizations (mean, maximum, minimum, and standard deviation) of team proactive personality revealed differential relationships with team climate for innovation. These findings suggest that team proactive personality can influence outcomes at different levels of analyses. Theoretical and practical implications of these findings are discussed. Practitioner points Team proactive personality (i.e., mean, maximum, and minimum) positively related to team climate for innovation. Team climate for innovation positively related to both individual creativity and job crafting. Team climate for innovation mediated the top‐down effects of team proactive personality on individual creativity and job crafting. Employers may consider proactive personality as one criterion at the stages of selecting and staffing of team members for creative jobs and creative team projects.